Evaluation of educational centers and quality - Sánchez Pérez, José Ignacio (Avances en Supervisión Educativa, 2007)
The evaluation of centres, internal or external, is an exigency for the permanent improvement of the educational systems and of the teaching institutions. It is necessary, from the educational supervision, to find an operative model of evaluation of the quality. This model is based on the concepts of efficacy, efficiency and functionality as basic dimensions of the quality.The evaluation facilitates the educative change in the way in which it promotes reflexive strategies that lead to the improvement of the organization and the operation of the processes.The evaluation of the centres will have to fulfil, at the same time, functions of control, rendering accounts, motivation, formation and support to the knowledge.Inspectorate plays a prevailing role in the internal and external evaluation of the centres, in the exercise of their characteristic functions (to advise, to supervise, to evaluate), being a key element to stimulate the evaluation processes and to get that it will be an habitual educative action.